A preliminary study of the siliceous and femic rock blocks in the Neoproterozoic diatexitic granite at Fuhu Hill in southwestern Guangdong, China. (17th January 2021) - Chen, Zhen; Liu, Yongjiang; Jin, Wei; Lou, Feng; Chen, Guoneng
Abstract : The crystalline basement of Cathaysia Block is commonly believed to have formed before the Middle Neoproterozoic; however, the basement rock has seldom been reported in the eastern Cathaysia. Recently, numerous siliceous and femic rock blocks distributed in the diatexitic host granite were observed on the rocky beach of Fuhu Hill in the southwestern Guangdong, China. The results of geological and geochemical investigations of these rock blocks revealed that the protolith of siliceous rock blocks (SRBs) was marine silicalite deposited in a pelagic environment between the ridge‐proximal and continental margin, and the femic rock blocks (FRBs) geochemically corresponded to trachybasalt and monzogabbro, pertaining to OIB/E‐MORB types in the Ce/Y‐Zr/Nb and Zr/Y/Nb systems. 206 Pb/ 238 U ages of 995 and 1, 002 Ma were obtained from zircon U–Pb dating of the FRBs. The host rocks of the SRBs and FRBs were mainly diatexitic granite that was intruded and sometimes hosted by massive granite. The zircon 206 Pb/ 238 U age gained from the diatexitic granite was 991 Ma whereas that from the massive granite was 239 Ma. It may be concluded that SRBs and FRBs were derived from a spilite‐keratophyre formation formed during 1, 005–995 Ma and disintegrated around 991 Ma due to crustal anataxis. These SRBs, FRBs, and their diatexitic host granite blocks might have been brought up to the shallow crust by granitic magma in the Indosinian period or due to fault activity in the late stage. Moreover, the southwest part of the eastern Cathaysia possessed a similar basement as the western Cathaysia. Abstract : The 1, 005–996 Ma femic rock blocks (FRBs) with thin‐bedded silicalite rock blocks (SRBs) hosted in the 991 Ma diatexitic granite were found in the southwest Guangdong, China. Those rock blocks were likely from a spilite‐keratophyre formation disintegrated during 991 Ma crustal anatexis, indicating that the eastern Cathaysia, at least its southwest part, has an identical basement with the western Cathaysia.